Microwave-assisted direct synthesis of some 5-alkyl-2-amino-1,3,4-thiadiazoles. - Thanh, Nguyen Dinh; Lan, Pham Hong; Minh Hai, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
Some 5-alkyl-2-amino-1,3,4-thiadiazoles have been synthesized by the MW-mediated solvent-free method. The reaction mixture is consisted of aliphatic acid, thiosemicarbazide and concentrated sulfuric acid (98%). Molar ratio of thiosemicarbazide and carboxylic acid was 1:2, reaction time was shortened (20 houres vs. 30 minutes). The structures of these aminothiadiazoles were confirmed by spectrospcopic methods (IR and 1H-NMR).